Zinc sulfide target material as well as preparation method and application thereof
By adding carbon element into zinc sulfide targets and using vacuum hot pressing process, the problems of complex preparation process and poor molding performance of zinc sulfide targets were solved, and a target with high conductivity and density was obtained, suitable for thin-film solar panels , simplifies processes and equipment and realizes industrial applications.
Patent Information
- Application Number
- CN202411256004.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-17
AI Technical Summary
The existing zinc sulfide target preparation process is complex, the equipment cost is high, the target molding performance is poor, the metal elements are easy to volatilize and oxidize, which affects the stability, and graphite molds affect the final performance.
0.04% to 2.6% of carbon element is added to zinc sulfide targets, and the preparation is carried out by vacuum hot pressing process to improve the molding performance and conductivity and stability of the target material, ignore the influence of graphite mold on performance, and produce high conductivity and density targets.
It realizes the high conductivity and density of the target material, simplifies the preparation process and equipment, is suitable for thin-film solar panels, and is suitable for industrial promotion.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal target materials, and in particular to a zinc sulfide target material and a preparation method and application thereof. Background Art
[0002] Zinc sulfide has good infrared transmittance and is widely used as an infrared optical material. The coating layer prepared by coating with zinc sulfide targets has the characteristics of high mechanical strength, high surface hardness and high stability. At present, polycrystalline zinc sulfide targets are mainly prepared by distillation process, but the process is complicated and the equipment cost is high, which makes it difficult to adapt to the growing market demand. In addition, zinc sulfide targets are also prepared by adding metal elements and using hot pressing, but the target molding performance is poor, the metal elements are easy to volatilize and oxidize during the production process, resulting in poor stability of the metal element content in the target, and the graphite mold will affect the final performance of the target.
[0003] Therefore, it is necessary to develop a technology to solve the above-mentioned technical problems existing in the prior art. Summary of the invention
[0004] Based on the defects of the prior art, the purpose of this application is to provide a zinc sulfide target material and a preparation method and application thereof.
[0005] To achieve the above objectives, in a first aspect, the present application provides a zinc sulfide target material, which includes the following components in weight percentage: C 0.04% to 2.6%, ZnS 97.4% to 99.96%.
[0006] Adding carbon to zinc sulfide targets has the following effects: (1) It can improve the molding properties of the targets. For example, when preparing targets by vacuum hot pressing, no pre-pressing is required, and the required pressure during vacuum hot pressing is relatively low; (2) It can improve the conductivity of the targets; (3) Carbon is very stable and is not easy to volatilize or oxidize at high temperatures, ensuring a stable C content in the targets during production; (4) When preparing targets by vacuum hot pressing, the influence of graphite molds on the final properties of the targets can be ignored, and graphite molds can be used directly for production. The resulting zinc sulfide targets have high conductivity and density, and are suitable for preparing thin-film solar panels. The preparation process and the equipment used are simple, making them easy to promote and apply in industrial applications.
[0007] The weight percentage of C in the zinc sulfide target is 0.04% to 2.6%, such as 0.04%, 0.05%, 0.08%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6% or a range formed by any two of the above.
[0008] The weight percentage of ZnS in the zinc sulfide target is 97.4% to 99.96%, such as 97.4%, 97.6%, 97.8%, 98.0%, 98.2%, 98.5%, 98.8%, 99.0%, 99.2%, 99.4%, 99.6%, 99.8%, 99.9%, 99.96% or the range formed by any two of the above.
[0009] Preferably, the zinc sulfide target material comprises the following components in weight percentage: C 0.1% to 1.8%, ZnS 98.20% to 99.90%. By controlling the contents of C and ZnS in the zinc sulfide target material within the aforementioned range, the relative density and conductivity of the target material can be better balanced.
[0010] Preferably, the C is graphite, which has high electrical conductivity and is cheap and readily available.
[0011] Preferably, the relative density of the zinc sulfide target is 97% to 99%, and the resistivity is 3800 to 4860 Ω·cm. The relative density of the zinc sulfide target can be selected as 97%, 97.1%, 97.2%, 97.3%, 97.4%, 97.5%, 97.6%, 97.7%, 97.8%, 97.9%, 98%, 98.1%, 98.2%, 98.3%, 98.4%, 98.5%, 98.6%, 98.7%, 98.8%, 98.9%, 99% or the range formed by any two of the above. The resistivity of the zinc sulfide target can be selected to be 3800-4860Ω·cm, such as 3800Ω·cm, 3850Ω·cm, 3900Ω·cm, 3950Ω·cm, 4000Ω·cm, 4050Ω·cm, 4100Ω·cm, 4150Ω·cm, 4200Ω·cm, 4250Ω·cm, 4300Ω·cm, 4350Ω·cm, 4400Ω·cm, 4450Ω·cm, 4500Ω·cm, 4550Ω·cm, 4600Ω·cm, 4650Ω·cm, 4700Ω·cm, 4750Ω·cm, 4800Ω·cm, 4860Ω·cm or a range formed by any two of the above.
[0012] More preferably, the relative density of the zinc sulfide target is 98% to 99%, and the resistivity is 4200 to 4600 Ω·cm, so as to achieve a better balance between the relative density and the resistivity.
[0013] The relative density of the zinc sulfide target can be measured by the following method: firstly, the volume of the target is measured according to the water displacement method, then the actual density is calculated according to formula (1), and then the relative density is calculated according to formula (2);
[0014] Actual density = target weight / target volume (1)
[0015] The actual density unit is kg / m 3 , target weight unit is kg, target volume unit is m 3 ;
[0016] Relative density = actual density / theoretical density * 100% (2)
[0017] The actual density unit is kg / m 3 , the theoretical density is kg / m 3 .
[0018] The resistivity of the zinc sulfide target material can be detected by a four-probe resistivity meter.
[0019] In a second aspect, the present application provides a method for preparing the zinc sulfide target, comprising the following steps:
[0020] The C powder and the ZnS powder are mixed in proportion and ball-milled to obtain a premix;
[0021] The premix is placed in a mold and subjected to vacuum hot pressing treatment, followed by cooling and processing to obtain a zinc sulfide target.
[0022] Preferably, the vacuum hot pressing treatment comprises the following specific steps:
[0023] Under the condition of vacuum degree <100Pa, heat to 820-1000℃ at a rate of 5-10℃ / min, keep warm for 15-40min, then pressurize to 40-50MPa within 20-60min, and keep warm and pressurized for 30-60min.
[0024] The hot pressing process can be carried out under the following vacuum conditions, such as 99Pa, 80Pa, 70Pa, 64.9Pa, 64Pa, 62Pa, 60Pa, 58Pa, 55Pa, 50Pa, 40Pa, 30Pa, 20Pa, 10Pa, 8Pa, 5Pa, 4Pa, 2Pa, 1Pa, 0.5Pa, 0.1Pa or any range formed by two of the above. Vacuum degree = atmospheric pressure - absolute pressure.
[0025] The heating rate of the hot pressing process can be selected to be 5°C / min, 5.5°C / min, 6°C / min, 6.5°C / min, 7°C / min, 7.5°C / min, 8°C / min, 8.5°C / min, 9°C / min, 9.5°C / min, 10°C / min or a range formed by any two of the above.
[0026] The holding temperature during the hot pressing process can be selected to be 820°C, 840°C, 860°C, 880°C, 900°C, 920°C, 940°C, 960°C, 980°C, 1000°C or a range formed by any two of the above.
[0027] The holding time during the hot pressing process can be selected to be 15min, 20min, 25min, 30min, 35min, 40min or a range formed by any two of the above.
[0028] The pressurization time during the hot pressing process can be selected to be 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes or a range formed by any two of the above.
[0029] The holding pressure during the hot pressing process can be selected to be 40MPa, 41MPa, 42MPa, 43MPa, 44MPa, 45MPa, 46MPa, 47MPa, 48MPa, 49MPa, 50MPa or a range formed by any two of the above.
[0030] During the hot pressing process, the heat preservation and pressure holding time after heating and pressurizing can be selected as 30min, 35min, 40min, 45min, 50min, 55min, 60min or a range formed by any two of the above.
[0031] Preferably, the specific steps of the vacuum hot pressing treatment are as follows:
[0032] Under the condition of vacuum degree of 0.1-30Pa, the temperature is raised to 860-900℃ at a rate of 5-10℃ / min, kept at this temperature for 30-40min, then pressurized to 45-50MPa within 20-30min, and kept at this temperature and pressure for 45-60min. The specific vacuum hot pressing process has higher adaptability to the influence of the forming effect caused by the fluctuation of C content in the target material, making the forming effect of the target material more stable, and the relative density of the target material is higher.
[0033] Preferably, the ball milling is three-dimensional homogeneous ball milling.
[0034] Preferably, the ball milling satisfies: the ball-to-material weight ratio is (2-5.5):1, the ball milling time is 3-10 hours, and the rotation speed is 40-80 r / min.
[0035] The ball-to-material mass ratio during the ball milling process can be selected to be 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or a range formed by any two of the above.
[0036] The ball milling time during the ball milling process can be selected to be 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or a range formed by any two of the above.
[0037] During the ball milling process, the rotation speed can be selected to be 40r / min, 45r / min, 50r / min, 55r / min, 60r / min, 65r / min, 70r / min, 75r / min, 80r / min or a range formed by any two of the above.
[0038] Preferably, the material of the mold is at least one of graphite and tungsten carbide.
[0039] In a third aspect, the present application provides an application of the zinc sulfide target in a thin-film solar panel.
[0040] Compared with the prior art, the beneficial effects of the present application are as follows: the present application can improve the formability and conductivity of the target material by adding a specific content of carbon element into the zinc sulfide target material, and the C content of the target material is stable during the production process. The hot pressing medium and graphite mold used in vacuum hot pressing have very little effect on the final performance of the target material. The target material preparation process and the equipment used are simple, and the prepared target material has high conductivity and density, and is suitable for preparing thin-film solar panels. DETAILED DESCRIPTION
[0041] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of the present application are all commonly used ordinary reagents and instruments unless otherwise specified.
[0042] Example 1
[0043] This embodiment provides a method for preparing a zinc sulfide target. The method for preparing a zinc sulfide target in this embodiment includes the following steps:
[0044] Graphite powder and ZnS powder were mixed in a mass ratio of 0.05:99.95, and three-dimensionally homogenized by ball milling to obtain a premix, wherein the ball-to-material weight ratio was 4:1, the ball milling time was 6 h, and the rotation speed was 60 r / min;
[0045] The obtained premix was loaded into a graphite mold and placed in a vacuum hot pressing furnace. The vacuum was evacuated to a vacuum degree of 40 Pa, the temperature was raised to 870°C at a rate of 8°C / min, and the temperature was kept for 35 minutes. Then, the pressure was increased to 45MPa within 25 minutes, and the temperature was kept for 50 minutes. After that, the zinc sulfide target was obtained by cooling and processing.
[0046] Example 2
[0047] This embodiment provides a zinc sulfide target material and a preparation method thereof. The difference between the preparation method of the zinc sulfide target material in this embodiment and that in embodiment 1 is that the mass ratio of graphite powder to ZnS powder is 0.10:99.90.
[0048] Example 3
[0049] This embodiment provides a zinc sulfide target material and a preparation method thereof. The difference between the preparation method of the zinc sulfide target material in this embodiment and that in embodiment 1 is that the mass ratio of graphite powder to ZnS powder is 0.95:99.05.
[0050] Example 4
[0051] This embodiment provides a zinc sulfide target material and a preparation method thereof. The difference between the preparation method of the zinc sulfide target material in this embodiment and that in embodiment 1 is that the mass ratio of graphite powder to ZnS powder is 1.8:98.20.
[0052] Example 5
[0053] This embodiment provides a zinc sulfide target material and a preparation method thereof. The difference between the preparation method of the zinc sulfide target material in this embodiment and that in embodiment 1 is that the mass ratio of graphite powder to ZnS powder is 2.5:97.5.
[0054] Example 6
[0055] This embodiment provides a method for preparing a zinc sulfide target. The method for preparing a zinc sulfide target in this embodiment includes the following steps:
[0056] Graphite powder and ZnS powder were mixed in a mass ratio of 0.05:99.95, and three-dimensionally homogenized by ball milling to obtain a premix, wherein the ball-to-material weight ratio was 4:1, the ball milling time was 6 h, and the rotation speed was 60 r / min;
[0057] The obtained premix was loaded into a graphite mold and placed in a vacuum hot pressing furnace. The vacuum was evacuated to a vacuum degree of 40 Pa, the temperature was raised to 820°C at a rate of 5°C / min, and the temperature was kept for 15 minutes. Then, the pressure was increased to 42MPa within 20 minutes, and the temperature was kept for 30 minutes. After that, the zinc sulfide target was obtained by cooling and processing.
[0058] Example 7
[0059] This embodiment provides a method for preparing a zinc sulfide target. The method for preparing a zinc sulfide target in this embodiment includes the following steps:
[0060] Graphite powder and ZnS powder were mixed in a mass ratio of 0.05:99.95, and three-dimensionally homogenized by ball milling to obtain a premix, wherein the ball-to-material weight ratio was 4:1, the ball milling time was 6 h, and the rotation speed was 60 r / min;
[0061] The obtained premix is loaded into a graphite mold and placed in a vacuum hot pressing furnace, evacuated to a vacuum degree of 40 Pa, heated to 860°C at a rate of 5°C / min, kept warm for 30 minutes, then pressurized to 45MPa within 20 minutes, kept warm and pressurized for 45 minutes, then cooled and processed to obtain a zinc sulfide target.
[0062] Example 8
[0063] This embodiment provides a method for preparing a zinc sulfide target. The method for preparing a zinc sulfide target in this embodiment includes the following steps:
[0064] Graphite powder and ZnS powder were mixed in a mass ratio of 0.05:99.95, and three-dimensionally homogenized by ball milling to obtain a premix, wherein the ball-to-material weight ratio was 4:1, the ball milling time was 6 h, and the rotation speed was 60 r / min;
[0065] The obtained premix is loaded into a graphite mold and placed in a vacuum hot pressing furnace, evacuated to a vacuum degree of 40 Pa, heated to 900°C at a rate of 10°C / min, kept warm for 40 minutes, then pressurized to 50MPa within 30 minutes, kept warm and pressurized for 60 minutes, then cooled and processed to obtain a zinc sulfide target.
[0066] Example 9
[0067] This embodiment provides a method for preparing a zinc sulfide target. The method for preparing a zinc sulfide target in this embodiment includes the following steps:
[0068] Graphite powder and ZnS powder were mixed in a mass ratio of 0.05:99.95, and three-dimensionally homogenized by ball milling to obtain a premix, wherein the ball-to-material weight ratio was 4:1, the ball milling time was 6 h, and the rotation speed was 60 r / min;
[0069] The obtained premix is loaded into a graphite mold and placed in a vacuum hot pressing furnace, evacuated to a vacuum degree of 40 Pa, heated to 1000°C at a rate of 10°C / min, kept warm for 40 minutes, then pressurized to 50MPa within 60 minutes, kept warm and pressurized for 60 minutes, then cooled and processed to obtain a zinc sulfide target.
[0070] Example 10
[0071] This embodiment provides a method for preparing a zinc sulfide target. The method for preparing a zinc sulfide target in this embodiment is different from that in Example 9 in that the obtained premix is loaded into a mold and placed in a vacuum hot pressing furnace, evacuated to a vacuum degree of 40 Pa, heated to 1000° C. at a rate of 10° C. / min, kept warm for 40 min, then pressurized to 60 MPa within 60 min, kept warm and pressurized for 60 min, then cooled and processed to obtain a zinc sulfide target.
[0072] Embodiment 11
[0073] This embodiment provides a method for preparing a zinc sulfide target. The method for preparing a zinc sulfide target in this embodiment is different from that in Example 9 in that the obtained premix is loaded into a mold and placed in a vacuum hot pressing furnace, evacuated to a vacuum degree of 40 Pa, heated to 1000° C. at a rate of 10° C. / min, kept warm for 40 min, then pressurized to 50 MPa within 60 min, kept warm and pressurized for 70 min, then cooled and processed to obtain a zinc sulfide target.
[0074] Comparative Example 1
[0075] This comparative example provides a method for preparing a zinc sulfide target material. The difference between the method for preparing a zinc sulfide target material in this comparative example and that in Example 1 is that the mass ratio of graphite powder to ZnS powder is 3:97.
[0076] Comparative Example 2
[0077] This comparative example provides a method for preparing a zinc sulfide target material. The difference between the method for preparing a zinc sulfide target material in this comparative example and that in Example 9 is that Ag powder is used to completely replace graphite powder, and the mass ratio of Ag powder to ZnS powder in this comparative example is 0.05:99.95.
[0078] The target materials obtained in the above examples and comparative examples were subjected to the following performance tests:
[0079] Relative density: The target volume is measured by the water displacement method, and then the relative density is calculated according to formulas (1) and (2);
[0080] Resistivity: Detected by four-probe resistivity meter.
[0081] The test results are shown in Table 1.
[0082] Table 1
[0083] Relative density / % Resistivity / Ω·cm Example 1 97.2 4860 Example 2 97.7 4510 Example 3 98.6 4214 Example 4 98.2 4081 Example 5 97.0 3810 Example 6 97.0 4780 Example 7 98.5 4522 Example 8 98.9 4430 Example 9 98.3 4560 Example 10 98.1 4523 Embodiment 11 98.0 4520 Comparative Example 1 96.8 3089 Comparative Example 2 96.2 4602
[0084] It can be seen from the above data that the relative density of the zinc sulfide target obtained in each embodiment of the present application is 97% to 99%, and the resistivity is 3800 to 4860Ω·cm, which is suitable for the preparation of thin-film solar panels. Comparative Example 1 has a low relative density due to excessive addition of graphite; Comparative Example 2 adds silver powder, and the relative density of the target is low, because the molding conditions of the silver powder target are harsh. From the comparison of Examples 1 to 5, it can be seen that when the weight percentage of carbon in the target is in the range of 0.10% to 1.8%, the relative density and resistivity of the target are better balanced, and the comprehensive performance of the target is better. From the comparison of Examples 1, 6 to 9, it can be seen that during the vacuum hot pressing process, the temperature is raised to 860 to 900°C at a rate of 5 to 10°C / min, and the temperature is kept for 30 to 40 minutes, and then pressurized to 45 to 50MPa within 20 to 30 minutes, and then kept warm and pressurized for 45 to 60 minutes, which is more conducive to the improvement of the relative density and conductivity of the target. Compared with Example 9, Examples 10 and 11 have a higher pressurization pressure or a longer holding time, but the relative density and resistivity of the obtained target materials are similar. It can be seen that the pressurization pressure of the present application is controlled within the range of 40 to 50 MPa, and the holding time is controlled within the range of 30 to 60 minutes, so that a target material with a suitable relative density and resistivity can be obtained.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A zinc sulfide target, characterized in that: The invention comprises the following components in percentage by weight: C 0.04% to 2.6%, ZnS 97.4% to 99.96%.
2. The zinc sulfide target material according to claim 1, characterized in that: The invention comprises the following components in percentage by weight: C 0.10% to 1.8%, ZnS 98.20% to 99.90%.
3. The zinc sulfide target material according to claim 1, characterized in that: The C is graphite.
4. The zinc sulfide target material according to claim 1, characterized in that: The relative density of the zinc sulfide target material is 98% to 99%, and the resistivity is 4200 to 4600 Ω·cm.
5. The method for preparing a zinc sulfide target according to any one of claims 1 to 4, characterized in that: The following steps are involved: The C powder and the ZnS powder are mixed in proportion and ball-milled to obtain a premix; The premix is placed in a mold and subjected to vacuum hot pressing treatment, followed by cooling and processing to obtain a zinc sulfide target.
6. The method for preparing a zinc sulfide target according to claim 5, characterized in that: The specific steps of the vacuum hot pressing treatment are as follows: Under the condition of vacuum degree <100Pa, heat to 820-1000℃ at a rate of 5-10℃ / min, keep warm for 15-40min, then pressurize to 40-50MPa within 20-60min, and keep warm and pressurized for 30-60min.
7. The method for preparing a zinc sulfide target according to claim 6, characterized in that: The specific steps of the vacuum hot pressing treatment are as follows: Under the condition of vacuum degree of 0.1-30Pa, the temperature is raised to 860-900°C at a rate of 5-10°C / min, kept at this temperature for 30-40min, then pressurized to 45-50MPa within 20-30min, and then kept at this temperature and pressure for 45-60min.
8. The method for preparing a zinc sulfide target according to claim 5, characterized in that: The ball milling is a three-dimensional homogeneous ball milling.
9. The method for preparing a zinc sulfide target according to claim 8, characterized in that: The ball milling satisfies: the ball-to-material weight ratio is (2-5.5):1, the ball milling time is 3-10 hours, and the rotation speed is 40-80 r / min.
10. Use of the zinc sulfide target material according to any one of claims 1 to 4 in thin-film solar panels.
Citation Information
Patent Citations
Cr-doping ZnS intermediate band thin film and preparation method thereof
CN111254402A
Preparation method of ZnS-doped target material
CN113136552A
Zinc sulfide-based sintering material, method for producing the same and sputtering target using the same
JP2001181045A
takes zinc oxide as a main component and contains n-type doping elements to form transparent and conductive properties
TW201107509A
Method for producing sputtering targets based on zinc sulfide and the said sputtering targets
TW428037B
